Effect of Diabetes Foot Care Education on Self –Efficacy Among Diabetes mellitus Patients Attending Embu and Kerugoya Level Five Hospitals, Kenya - Mbisi, Annastacia Munzi; Gitonga, Lucy; Gichobi, Beth (British Journal of Healthcare and Medical Research, 2025)
Diabetic foot (DF) remains a leading cause of disability, amputations, and premature mortality among individuals with diabetes, yet much of its burden is preventable through education and effective self-care practices. Beyond knowledge, prevention requires strengthening self-efficacy—the confidence to adopt and maintain protective foot care behaviors. This study evaluated the impact of structured diabetes foot care (DFC) education, guided by Bandura’s self-efficacy theory, on foot care self-efficacy among patients with diabetes in Kenya. A quasi-experimental design was employed at Embu and Kerugoya Level Five Hospitals, enrolling 230 participants randomly assigned to intervention (n=115) and control (n=115) groups. The intervention group received monthly interactive DFC sessions for three months, reinforced by follow-up phone calls, while the control group continued with routine care. Self-efficacy was assessed at baseline and post-intervention using the Diabetes Foot Care Self-Efficacy Scale, which measures magnitude, strength, and generality. At baseline, both groups exhibited low to moderate self-efficacy levels. However, after the intervention, significant improvements were observed in the intervention group across all domains: magnitude (2.85→4.23, p<0.001), strength (2.54→4.33, p<0.001), and generality (2.05→4.27, p<0.001), while the control group demonstrated only modest changes. These findings highlight that structured foot care education, reinforced through follow-up support, substantially improves patients’ confidence and ability to sustain preventive foot care behaviors. Integrating such approaches into routine diabetes care, complemented by community and digital follow-up strategies, offers a feasible pathway to reducing diabetic foot complications in resource-limited settings.